2008
DOI: 10.1016/j.ygyno.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical, and treatment trends among women diagnosed with vulvar cancer in the United States

Abstract: Objective-Describe the treatment and survival patterns among a population-based sample of vulvar cancer patients diagnosed in the U.S. in 1999.Methods-Cases were identified for the National Cancer Institute's Patterns of Care Study (POC) using Surveillance, Epidemiology, and End Results Program (SEER). A stratified random sample of non-Hispanic white, non-Hispanic black, and Hispanic women age 20 and older was selected from cases reported by eleven SEER registries. Analyses of the association between vulvar ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 19 publications
3
62
2
3
Order By: Relevance
“…Furthermore, younger patients in Germany are diagnosed more often with early tumour stages [14]. While other studies have shown that more advanced tumour stages are mainly found in older patients [13,15], this could not be confirmed by the present data. The literature reports contradictory findings on the influence of age on prognosis: While Kumar et al has observed an influence in his SEER data analysis [5], others did not [16].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Furthermore, younger patients in Germany are diagnosed more often with early tumour stages [14]. While other studies have shown that more advanced tumour stages are mainly found in older patients [13,15], this could not be confirmed by the present data. The literature reports contradictory findings on the influence of age on prognosis: While Kumar et al has observed an influence in his SEER data analysis [5], others did not [16].…”
Section: Discussioncontrasting
confidence: 95%
“…However, the present group of patients was clearly different from the SEER patients; the share of patients with LN metastases (21%) and distant metastases (3%) was significantly lower. Furthermore, no differences were found between the groups regarding the tumour stages, whereas the frequency of advanced tumour stages (FIGO III/ IV) varied significantly between the groups in the study by Kumar et al (26% vs. 39%) [5], which, however, was not reproduced in another analysis of the SEER data [15]. …”
Section: Discussionmentioning
confidence: 95%
“…In the United States the highest incidence of vulvar cancer was reported in white women compared to black patients, Hispanic women and Asian/Pacific Islander [20]. Moreover, during the last decade a lack of changes in the age-adjusted incidence and mortality rate of vulvar malignancy was reported in the United States and Germany [6,21,22,23]. These results are in contrast with ours, which show a significant decrease in incidence but an increase in mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Vulvar squamous cell carcinoma (VSCC) is an uncommon disease, constituting 3% to 5% of all malignancies in the female genital tract (1,2). VSCC develops primarily in elderly women, after their 70s; however, the number of cases in younger patients has been climbing, likely due to human papillomavirus (HPV) infection (2).…”
Section: Introductionmentioning
confidence: 99%